Transitioning towards circular economy through municipal solid waste analysis and characterisation using SowaCLINK software - Onungwe, Ishmael; Hunt, Dexter V. L.; Jefferson, Ian (Frontiers in Sustainability, 2024)
Municipal solid waste constitutes environmental challenges globally, especially in developing countries, due to increasing waste generation, population growth, inadequate infrastructure, lack of data and poor planning. This study aims to conduct a comprehensive waste audit on the municipal solid waste generated in Aba, a metropolis in southeastern Nigeria. Aba is a commercial city considered the messiest because of the massive municipal solid waste generation and poor management. The study investigated the energy potential and waste regeneration. Municipal solid waste data was sought to provide insight into the quantity and composition of municipal solid waste. The methodology was site-based, in line with the standard test method for determining unprocessed municipal solid waste (ASTM-D5231-92) and SowaCLINK software, a computer-based environmental application, was used for characterisation. Linear extrapolation was adopted to quantify the rate of municipal solid waste generated. The geometric mean was applied to forecast the area's population for a 10-year design period. The chemical elements of the characterised municipal solid waste were utilised based on the ASTM-D5291 standard for municipal solid waste thermochemical conversion, and the high and low heating values were analysed. The outcomes provided energy recovery potential, the electrical power potential, and the power to the grid of electrical power of the municipal solid waste. The results obtained were 0.7813kg/p/d and 490268t/y for a population of 1,719,185 persons. The percentage of the municipal solid waste components with energy potential was 71%, comprising 48% combustible and 23% organic components on average. The high heating value computed was 176.5MJ/kg, and the low heating value was 14MJ/kg. The energy recovery potential was 3709463 MWh, the electrical power potential was 38680 MW, and the power to the grid was 26.1 MW daily. The research reveals a promising direction in transitioning from the linear economy of municipal solid waste management towards implementing an integrated sustainable municipal solid waste management based on the circular economy model. The study recommends adopting detailed steps to proffer solutions to the environmental challenges associated with municipal solid waste in most low-middle-income countries to achieve sustainable municipal solid waste management while generating electricity and bio-fertilizers through incineration and anaerobic digestion.